Now you see it, now you don't interests, issues, and psychological distance in integrative negotiation. [article]. - Giacomantonio, Mauro
Neotiators are often advised to seek win-win agreements by focusing on interests (primary features) rather than issues (secondary features) but whether such advise is valid remains to be seen. Consistent with construal level theory(Y. Trope & N. Liberman, 2003). Experiment 1 and 2 shows that negotiators focus on secondary features (issues) more than on primary features (interests) when psychological distance is low rather than high, and concomitant construal level is local and specific rather than global and abstract. Experiment 3 showed that high construal level promoted problem-solving behavior and therefore facilitated the achievement of win-win agreement, but only when an integrative potential resided in underlying interests:when integrative potential resided in the issues, low construal level negotiators achieved higher joint outcomes. Thus, both low-and high-construal negotiators may achieve win-win agreements when such agreements require trade-offs at the level of issues, or at the level of underlying interests, respectively.
Keywords: Contrual level; Underlying interest; Negotiation